Меню

УСЛОВИЕ:
Раскройте скобки, приведите подобные слагаемые: (3x + y) - (-x - 4y)

(x + 6y) - (8x - 7y)

(m + n) - ( m - n)

( m + 3) - (6m +5) - (m -1)

(x - y) + (x - y) - (2x + y)

(0,2x - 3) - ( x - 2) - (0,4x - 1)


РЕШЕНИЕ:

(3x+y)-(-x-4y)=3x+y+x+4y=4x+5y
(x+6y)-(8x-7y)=x+6y-8x+7y=-7x+13y
(m+n)-(m-n)=m+n-m+n=2n
(m+3)-(6m+5)-(m-1)=m+3-6m-5-m+1=-6m-1
(x-y)+(x-y)-(2x+y)=2x-2y-2x-y=-3y
(0.2x-3)-(x-2)-(0.4x-1)=0.2x-3-x+2-0.4x+1=-1.2x

$$ 1)(3x + y) - (-x - 4y)=3х+у+х+4у=4х+5у; \\ 2)(x + 6y) - (8x - 7y)=х+6у-8х+7у=13у-7х; \\ 3)(m + n) - ( m - n)=m+n-m+n=2n; \\ 4)( m + 3) - (6m +5) - (m -1)=m+3-6m-5-m+1=-1-6m; \\ 5)(x - y) + (x - y) - (2x + y)=x-y+x-y-2x-y=-3y; \\ 6)(0,2x - 3) - ( x - 2) - (0,4x - 1) = 0,2х-3-х+2-0,4х+1= -1,2х $$






Похожие примеры: